Psychiatric symptoms and comorbidities in patients with drug-resistant epilepsy in presurgical assessment—A prospective explorative single center study - Friedrich, Fabian; Pataraia, Ekaterina; Aull-Watschinger, Susanne; Zehetmayer, Sonja; Weitensfelder, Lisbeth; Watschinger, Clara; Mossaheb, Nilufar (Frontiers in Psychiatry, 2022)
Introduction: People with epilepsy (PWE) have a higher prevalence of psychiatric disorders. Some individuals with drug-resistant epilepsy might benefit from surgical interventions. The aim of this study was to perform an assessment of psychiatric comorbidities with a follow-up period of 12 months in patients with drug-resistant epilepsy, comparing those who underwent surgery to those who did not. Material and Methods: We assessed psychiatric comorbidities at baseline, after 4 months and after 12 months. Psychiatric symptoms and diagnoses were assessed using SCID-Interview, Hamilton Rating Scale for Depression, Beck-Depression Inventory, Hamilton Anxiety Rating Scale, Prodromal-Questionnaire and the Global Assessment of Functioning Scale. Results: 25 patients were included in the study, 12 underwent surgery, 11 were esteemed as being neurologically unqualified for surgery and 2 refused surgery. Patients in the no-surgery group were significantly older, reported more substance use, had significantly higher levels of anxiety and were more often diagnosed with a personality disorder. Age and levels of anxiety were significant predictors of being in the surgery or the no-surgery group. The described differences between surgery and no-surgery patients did not change significantly over the follow-up period. Discussion: These data point towards a higher expression of baseline psychiatric symptoms in drug-resistant PWE without surgery. Further studies are warranted to further elucidate these findings and to clarify potential psychotropic effects of epilepsy itself, drug-resistant epilepsy and of epilepsy surgery and their impact on psychopathology. Clinically, it seems highly relevant to include psychiatrists in an interdisciplinary state-of-the-art perioperative management of drug-resistant PWE.